Population Pharmacokinetics of Tenofovir in Pregnant and Postpartum Women Using Tenofovir Disoproxil Fumarate - Eke, Ahizechukwu C.; Shoji, Kensuke; Best, Brookie M.; Momper, Jeremiah D.; Stek, Alice M.; Cressey, Tim R.; Mirochnick, Mark; Capparelli, Edmund V. (Antimicrobial Agents and Chemotherapy, 2021)
Pharmacokinetics of drugs can be affected by physiologic changes during pregnancy. Our aim was to assess the influence of covariates on tenofovir (TFV) pharmacokinetics in pregnant and postpartum women receiving tenofovir disoproxil fumarate (TDF). Pharmacokinetics of drugs can be affected by physiologic changes during pregnancy. Our aim was to assess the influence of covariates on tenofovir (TFV) pharmacokinetics in pregnant and postpartum women receiving tenofovir disoproxil fumarate (TDF). Population pharmacokinetic parameter estimates and the influence of covariates were assessed using nonlinear mixed-effects modeling (NONMEM 7.4). Forty-six women had intensive pharmacokinetic evaluations during the second and third trimesters of pregnancy, with another evaluation postpartum. A two-compartment pharmacokinetic model with allometric scaling for body weight and first-order absorption best described the tenofovir plasma concentration data. Apparent oral clearance (CL/F) and volume of distribution at steady state ( V ss /F) were increased during pregnancy. Weight, serum creatinine (SCr), pregnancy, albumin, and age were associated with TFV CL/F during univariate assessment, but in the multivariate analysis, changes in CL/F and V ss /F were only associated with increased body weight and enhanced renal function. Due to greater weight and lower SCr during pregnancy, CL/F was 28% higher during pregnancy than postpartum. In the final model, CL/F (liters per hour) was described as 2.07 × (SCr/0.6) 0.65 × weight 0.75 , with a low between-subject variability (BSV) of 24%. The probability of target attainment (proportion exceeding area under the concentration-time curve of >1.99 μg·h/ml, the 10th percentile of average TFV exposure for nonpregnant historical controls) was 68%, 80%, 87%, and 93% above the target with 300 mg, 350 mg, 400 mg, and 450 mg of TDF, respectively, during pregnancy and 88%, 92%, 96%, and 98% above the target with same doses in postpartum women. Dose adjustment of TDF during pregnancy is not generally warranted, but any modification should be based on weight and renal function. (This study has been registered at ClinicalTrials.gov under identifier NCT00042289.)